Selective halogenation of pyridines using designed phosphine reagents - Levy, JN; Alegre-Requena, JV; Liu, R; Paton, RS; McNally, A (American Chemical Society, 2020)
Halopyridines are key building blocks for synthesizing pharmaceuticals, agrochemicals, and ligands for metal complexes, but strategies to selectively halogenate pyridine C–H precursors are lacking. We designed a set of heterocyclic phosphines that are installed at the 4-position of pyridines as phosphonium salts and then displaced with halide nucleophiles. A broad range of unactivated pyridines can be halogenated, and the method is viable for late-stage halogenation of complex pharmaceuticals. Computational studies indicate that C–halogen bond formation occurs via an SNAr pathway, and phosphine elimination is the rate-determining step. Steric interactions during C–P bond cleavage account for differences in reactivity between 2- and 3-substituted pyridines.